Preparation And Evaluation Of Microporous Drug Delivery System - GOWDA.D.V., KHAN M. S; NAWAZ MOHAMMED; SHIVAKUMAR H.G. (International Journal of Pharma and Bio Sciences, 2010)
The aim of the present study was to prepare and evaluate microporous pellets loaded with Indapamide (IP) using blend of Avicel PH 101 (Microcrystalline cellulose) and sodium chloride (NaCl) by extrusion/spheronization technique for controlled release. Solid, discrete, reproducible pellets were obtained. Sieve analysis data indicated that the size of prepared pellets were in the range of 1135 µm to 1245µm. Prepared pellets were spherical in shape, have dent surfaces with pores on the surface, as evidenced by scanning electron microscopy (SEM). The pellets were characterized for micromeritic properties and encapsulation efficiency. Molecular level drug distribution and compatibility of the drug after encapsulation in the pellets were confirmed by differential scanning calorimetry (DSC) and by Fourier-transform infrared (FTIR). The prepared pellets were analyzed quantitatively for the amount of encapsulated drug. Studies such as drug loading, encapsulation efficiency and in vitro drug release indicated F3 as optimized formulation. The optimum formulation F3 shows 91.41 % drug release up to 24 h. It was also observed that, there was no significant release of drug in gastric pH. The release kinetics for all the formulations indicated that drug release followed non-Fickian diffusion. The stability studies performed on F3 showed no significant difference in drug content. It was concluded that the drug release performance was greatly affected by the polymer and pore forming agent used in preparation of pellets.